Photo-Oxygenation as a New Therapeutic Strategy for Neurodegenerative Proteinopathies by Enhancing the Clearance of Amyloid Proteins - Tomizawa, Ikumi; Nakagawa, Hanako; Sohma, Youhei; Kanai, Motomu; Hori, Yukiko; Tomita, Taisuke (Frontiers in Aging Neuroscience, 2022)
Alzheimer disease (AD) is associated with the aggregation of two amyloid proteins: tau and amyloid-β (Aβ). The results of immunotherapies have shown that enhancing the clearance and suppressing the aggregation of these two proteins are effective therapeutic strategies for AD. We have developed photocatalysts that attach oxygen atoms to Aβ and tau aggregates via light irradiation. Photo-oxygenation of these amyloid aggregates reduced their neurotoxicity by suppressing their aggregation both in vitro and in vivo. Furthermore, photo-oxygenation enhanced the clearance of Aβ in the brain and microglial cells. Here, we describe the effects of photo-oxygenation on tau and Aβ aggregation, and the potential of photo-oxygenation as a therapeutic strategy for AD, acting via microglial clearance.